Developmental temperature predicts the adult response to stressors in a free‐living passerine. Issue 3 (2nd December 2019) - Uehling, Jennifer J.; Taff, Conor C.; Winkler, David W.; Vitousek, Maren N.
Abstract: Early‐life conditions can have substantial effects on the ways animals respond to stressors as adults. In particular, thermal conditions during development affect juveniles' responses to stressors, and there is evidence that these effects may extend into adulthood. However, these effects remain poorly understood, especially in free‐living organisms. We test the prediction that ambient temperatures during laying, embryonic development and nestling development affect the hormonal mediators of the response to stressors in adults. To do so, we use a long‐term dataset of tree swallows ( Tachycineta bicolor ) with records from both natal development and adult breeding. We found a strong, negative relationship between ambient temperature during early development (incubation) and an individual's corticosterone (CORT) response to stress later in life (while incubating her own young). Thermal conditions during other stages of natal development also showed a weak relationship with baseline CORT during provisioning. In a post hoc analysis, we found no evidence that ambient temperature during development differentially influenced the survival and recruitment of juveniles with different CORT phenotypes. Our results show that thermal conditions during development can have long‐term effects on how individuals respond to stressors. Abstract : Using a long‐term dataset with breeding and hormone data from a free‐living passerine, the authors found a negative relationship between temperature during development and adult glucocorticoid response to stressors. The results show that thermal conditions during development can have long‐term effects on how individuals respond to stress (Photo Credit: David Chang van Oordt).